PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan LQ-45 Yang Terdaftar Di Bursa Efek Indonesia Periode Februari 2010-Januari 2015) - Suroto Suroto (FEB UNTAG Semarang, 2015)
The aim of this study is to examine effect of investment decisions, financing decisions and dividend policy on firm value of companies in the LQ-45 index listed on the Indonesia Stock Exchange in the period Februari 2010 to January 2015. The sample are taken by purposive sampling. The sample is 16 companies with sum observation 80. The analysis tehnique in study used multiple regression ordinary least square with α = 0,05. Based on results of data analysis show that Investment decisions significant positive affects on firm value, Financing decisions significant negative affects on firm value and Dividend policy has negative not significant effect on firm value. Keyword : firm value, investment decisions, financing decisions, dividend policy.